Microglial Janus kinase/signal transduction and activator of transcription 3 pathway activity directly impacts astrocyte and spinal neuron characteristics - Molet, Jenny; Mauborgne, Annie; Diallo, Mickael; Armand, Vincent; Geny, David; Villanueva, Luis; Boucher, Yves; Pohl, Michel (Journal of neurochemistry, 2016)
After peripheral nerve injury microglial reactivity change in the spinal cord is associated with an early activation of Janus kinase (JAK)/STAT3 transduction pathway whose blockade attenuates local inflammation and pain hypersensitivity. However, the consequences of microglial JAK/STAT3-mediated signaling on neighboring cells are unknown. Using an in vitro paradigm we assessed the impact of microglial JAK/STAT3 activity on functional characteristics of astrocytes and spinal cord neurons. Purified rat primary microglia was stimulated with JAK/STAT3 classical activator interleukin-6 in the presence or absence of a selective STAT3 inhibitor and rat primary astrocytes or spinal cord neurons were exposed to microglia conditioned media (CM). JAK/STAT3 activity-generated microglial CM modulated both astrocyte and neuron characteristics. Beyond inducing mRNA expression changes in various targets of interest in astrocytes and neurons, microglia CM activated c-Jun N-terminal kinase, STAT3 and NF-κB intracellular pathways in astrocytes and promoted their proliferation. Without modifying neuronal excitability or survival, CM affected the nerve processes morphology and distribution of the post-synaptic density protein 95, a marker of glutamatergic synaptic contacts. These findings show that JAK/STAT3 activity in microglia impacts the functional characteristics of astrocytes and neurons. This suggests its participation in spinal cord tissue plasticity and remodeling occurring after peripheral nerve injury. We show that the activity of JAK/STAT3 pathway in microglial cells confers them a specific signaling modality toward neighboring cells, promoting astrocyte proliferation and changes in neuronal morphology. These in vitro data suggest that the early JAK/STAT3 activation in spinal cord microglia, associated with peripheral nerve injury, participates in functional alteration of various cell populations and in spinal tissue remodeling.
Keywords: Animals; Female; astrocyty; Spinal Cord; ženské pohlaví; STAT3 Transcription Factor; cell plasticity; mícha; mikroglie; neurony; Janus kinasy; signální transdukce; kultivované buňky; Signal Transduction; Astrocytes; Janus Kinases; Rats, Sprague-Dawley; Neurons; Cells, Cultured; transkripční faktor STAT3; astrocytes; Microglia; potkani Sprague-Dawley; microglia conditioned media; krysa rodu Rattus; zvířata; spinal cord neurons; JAK/STAT3 pathway; Rats